Global double hybrids do not work for charge transfer: A comment on "Double hybrids and time‐dependent density functional theory: An implementation and benchmark on charge transfer excited states". Issue 8 (7th January 2021) - Casanova‐Páez, Marcos; Goerigk, Lars
Abstract: We comment on the results published by Ottochian et al. in J. Comput Chem . 2020, 41, 1242. Therein, the authors claim that the second‐order, perturbative correlation correction applied to the time‐dependent version of the PBE‐QIDH global double‐hybrid functional approximation (DHDFA) enables the description of charge‐transfer (CT) excitations. Herein, we point out some inadvertent oversights related to what had already been previously known and achieved in the field of time‐dependent DHDFAs. Exemplified for the same four systems that Ottochian et al. have used to analyze intermolecular CT excitations, we show how a systematic and unacceptably large redshift in global DHDFAs is rectified when using the latest long‐range corrected DHDFAs published earlier in J. Chem. Theory Comput . 2019, 15, 4735. Abstract : This comment corrects the inadvertently given, incomplete account of previous developments, and insights in the field of time‐dependent double‐hybrid density functionals given in J. Comput. Chem . 2020, 41, 1242, and disproves the therein made claim that global double hybrids are able to describe charge‐transfer excitations.